KOMPETENSI BADAN PERMUSYAWRATAN DESA DALAM PROSES PENYUSUNAN PERATURAN DESA STUDI DI DESA GAMSIDA KECAMATAN IBU SELATAN KABUPATEN HALMAHERA BARAT - IDU, ANDRISTAN; LENGKONG, FLORENCE; PLANGITEN, NOVVA (Sam Ratulangi University, 2021)
Based on the background of the problem that the Village Consultative Council still does notunderstand and understand the work being carried out, this research aims are: to determine the competence ofthe Village Consultative Body in the process of drafting the study village regulations in Gamsida Village,South Mother District, West Halmahera Regency. In this study, the author uses a descriptive type which aimsto describe and carefully describe social phenomena or realities by describing or describing the problemsstudied qualitatively. To obtain information that is in accordance with the problems studied about thecompetence of the village consultative body (BPD) in the process of drafting village regulations, techniquesare used in an effort to collect data, namely through interviews, observations and documentation. The resultsof the study show that the competence of the village consultative body is a very important institution in theimplementation of the preparation of village regulations, one of the success objectives of the competence isthe extent to which the competence of the village consultative body is improved. The competence of thevillage consultative body is also an effort to improve the quality of life and life as much as possible for thewelfare of the village community.Keywords: Competence, Village Consultative Body, Village Regulation